(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2017)
In plywood plants, the bark of a birch tree is a readily accessible and already concentrated feedstock for further processing. It consists of two distinct layers: outer bark and inner bark. Up to 25.7 % of biologically active compounds (betulin, lupeol, betulinic acid) are concentrated in outer bark, with a broad spectrum of applications in the chemical, pharmaceutical, cosmetic and food industries. The inner bark must be separated from outer bark as well as possible because it causes a decrease in the yield and purity of the prepared ethanol extractives. Therefore, it is very important to predict the content of inner bark in the feedstock taken for the extraction process. A novel method for the characterization of feedstock was developed using the higher heating value (HHV) as a reference. The developed method for birch outer bark quality control is very useful in birch outer bark extraction plants. Thus, it would be possible to control the purity of the feedstock and to predict the potential yield of extractives as well as the amount of the solvent to be taken for the extraction process. Pure enough (≥90 % of outer bark) feedstock for biologically active extractives production can be obtained by the floating method after 5 h if the HHV is more than 32-33 MJ/kg.